Analisis Pengaruh Service Quality, Personal Selling dan Complain Handling Melalui Satisfaction Serta Trust terhadap Customer Retention (Survei Nasabah Tabungan Bank Harda Internasional Cabang Pontianak) - Lay, Nico Yudhinata; Listiana, Erna; Heriyadi, Heriyadi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2018)
This study aims to determine the effects of service quality, personal selling and complain handling through satisfaction and trust on customer retention on the customer of Harda International Savings Bank, in Pontianak branch. The sample of this study consisted of 100 respondents of customers of Harda International Savings Bank, Pontianak. This associative study employed a survey method and a path analysis. The results of hypothesis test using test-F shows that the variables of service quality, personal selling, and complain handling have significant influence on satisfaction. Likewise the t-test results of hypothesis shows the variables of service quality, personal selling, and complain handling significantly influence satisfaction. Subsequently, satisfaction variable has significant influence on trust and customer retention. Meanwhile, trust variable has significant influence on customer retention.